Social Forestry Governance and Community Economic Development: The Role of Environmental Quality in the Fifty Cities Regency - Wijayanty, Ria; Muchtar, Bustari; ., Marwan (Journal of Cultural Analysis and Social Change, 2026)
Rural forest-based communities frequently remain economically vulnerable despite expanded access to forest resources, indicating that welfare improvement depends on more than tenure security alone. Addressing this critical gap, this study investigates how Social Forestry and Human Resource Quality influence Community Economic Welfare through the mediating role of Environmental Quality in Kabupaten Lima Puluh Kota, Indonesia. Adopting a quantitative research design, the study focuses on Silver-category Social Forestry Business Groups (KUPS) as a strategic transitional stage of institutional development. Data were collected from 310 respondents and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The measurement model demonstrates strong reliability and discriminant validity, supporting robust structural analysis. The findings reveal that Social Forestry has a significant positive effect on Environmental Quality and directly enhances Community Economic Welfare. In contrast, Human Resource Quality significantly improves Environmental Quality but does not exert a direct influence on economic welfare. Environmental Quality plays a decisive role by significantly strengthening Community Economic Welfare and mediating the effects of both Social Forestry and Human Resource Quality. These results highlight that ecological improvement is not a peripheral outcome but a central development mechanism through which institutional reform and capacity building generate welfare gains. This study contributes conceptually by repositioning environmental quality as an active transmission channel of development and methodologically by integrating governance, human capital, and ecological dimensions within a unified SEM-PLS framework. In a broader context, the findings suggest that social forestry policies should prioritize ecological performance and embed capacity development within environmental governance to support sustainable rural development and green economy agendas.